Pemanfaatan E-Commerce Dalam Pemasaran Produk Minyak Jelantah (Mijel) - Suherman Suherman; Minarwati Dewi; Andi Bustan; Maya Mustika; Septaria Yolan Kalalinggi; Lia Septya (UNIB Press, 2024)
E-commerce will be a strong indispensabe business structure in moments’s and arising information age. But some people do not understand the benefits of using electronic commerce. So that the fidelity was carried out to introduce the use of e-commerce, Market Place, and Online Shop to PKK maters in Menteng in vill. The socialization was held on Sunday, October 25, 2023 in Menteng sub-district, which was attended by 14 PKK maters. This service began with socialization of the Application of E-Commerce, Market Place and Online Shop and continued with discussion. Participants were veritably enthusiastic during the question and answer session, this was shown by the average pre-test results from 65% to 98% (post-test). So it can be concluded that PKK maters are enthusiastic about exercising and understanding the benefits and uses of e-commerce, Market Place and Online Shop. This training is important so that PKK maters can make good use of various types of electronic commerce for their mijel products and other business products.